PENGARUH CITRA WISATA DAN DAYA TARIK TERHADAP KEPUTUSAN BERKUNJUNG PADA OBJEK WISATA VELANGKANNI MEDAN - Rosita Hileria Purba; Nursiah Nursiah (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2025)
Graha Maria Annai Velangkanni plays an important role as an icon of Medan City as well as a tourist destination that attracts visitors due to its historical value and beauty, contributing to the development of the local tourism industry. From January to April 2025, the number of tourist visits to this site fluctuated, which became the main focus of this study. Factors influencing tourists’ decisions to visit include tourism image and tourist attractions, considered key aspects in visitor preferences. This study aims to analyze the effect of tourism image and tourist attractions on the decision to visit Graha Maria Annai Velangkanni in Medan. The research employed a quantitative method, collecting primary data through survey questionnaires and literature review. Data analysis included validity and reliability tests, classical assumption tests, hypothesis testing using multiple linear regression, t-tests, F-tests, and calculation of the coefficient of determination (Adjusted R²) with a sample of 100 respondents. The results of the multiple linear regression showed a positive effect, with regression coefficients of 0.315 for tourism image and 0.845 for tourist attractions. The t-test results indicated t-values of 2.884 (p=0.005) for tourism image and 12.932 (p=0.001) for tourist attractions. The F-test produced an F-value of 100.429 with a significance of 0.001. These findings confirm that tourism image and tourist attractions have a positive and significant influence, both partially and simultaneously, on tourists’ decisions to visit Graha Maria Annai Velangkanni in Medan.